Criminal Law - Samaha, Joel (Thomson Wadsworth, 2005)
The Study Guide is designed to help students learn chapter concepts. It includes chapter-specific learning objectives, chapter summaries and detailed outlines, key terms, and chapter self-tests that include multiple-choice, true/false and essay questions.